Potencial antioxidante de extratos hidroalcoólicos de mirtilo, polpa de açaí e goji berry: efeito na estabilidade oxidativa e sensorial em queijo petit suisse - Moura, Cristiane de (2016)
The consumer interest in healthy foods with high amounts of antioxidants is one of the important factors for reducing the risk of disease and it has encouraged researchers and industry to develop innovative and functional products and ingredients. To that end, the objective of this research was to study the bioactive compounds present in the acai pulp, blueberry and goji berry samples, as well as the phenolic compounds form of extraction using the response surface methodology (RSM), antioxidant and antimicrobial activity of it, identification and quantification of compounds by high-performance liquid chromatography (HPLC) and, at the end, the development of petit suisse cheeses added with freeze-dried extracts of the samples. A 2³ factorial design was used to analyze the solvent effect (ethanol and water), time (30 and 60 min) and temperature (30 °C and 60 °C) on the extraction and determination of total phenolic compounds (TPC) and antioxidant activity (AA). The variables time and temperature had a positive effect on the antioxidant activity (AA) in their highest levels with 60 min and 60 °C respectively. The ethanol solvent 80 % is more efficient in TPC extraction with AA in all arrays. The identification of phenolic compounds performed by HPLC revealed the presence of catechin, epicatechin, rutin, myricetin, chlorogenic acid, coumaric acid and ferulic acid. Regarding the AA the acai pulp showed higher activity in vitro when extracted by 60 °C for 60 min, but none of the three extracts analyzed under these conditions showed antibacterial activity against Staphylococcus aureus and Salmonella bongori in the concentrations tested (95.00 to 2.34 mg/mL. For petit suisse cheeses added with phenolic extract of the samples, the sample containing goji berry achieved greater sensory acceptance among judges (75.67%), second only to the commercial sample used for comparison with 91.56 % of acceptance. In relation to the storage time, the oxidation was evaluated by the level of thiobarbituric acid reactive substances and color analysis. Both analysis were satisfactory, making the extracts addition an alternative to preserve the product properties and give it a high content of bioactive and nutritive compounds.